Central odontogenic fibroma of the mandible - V Chhabra; A Chhabra (Wolters Kluwer Medknow Publications, 2012)
Central odontogenic fibroma (COF) is an extremely rare benign tumor that accounts for 0.1% of all odontogenic tumors. It appears as an asymptomatic expansion of the cortical plate of the mandible or maxilla. Radiologically it presents as a unilocular or multilocular radiolucency. It responds well to surgical enucleation with no tendency for recurrence. We describe a case of COF in mandibular right posterior region in a 16-year-old female. The lesion was surgically removed and analyzed histopathologically.